2022
DOI: 10.1002/inf2.12305
|View full text |Cite
|
Sign up to set email alerts
|

Air sensitivity of electrode materials in Li/Na ion batteries: Issues and strategies

Abstract: With the development of electrode materials in lithium ion batteries-upgrading from LiCoO 2 and LiFePO 4 to Ni-rich layered oxides, and the shifting of battery systems from high cost lithium ion to low cost sodium ion technology, the air sensitivity of the electrode materials has become an increasingly important issue in both production and application. Furthermore, the air sensitivity of electrode materials must be carefully considered throughout nearly all stages of their life, including material design, syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 121 publications
1
33
0
Order By: Relevance
“…S1) showed that the NNSO-E sample had the same peaks at 117, 166, and 1073 cm −1 as the Na 2 CO 3 that was also exposed to the air under the same conditions. Therefore, the impurities on the surface are possibly composed of Na 2 CO 3 •nH 2 O, NaHCO 3 •nH 2 O, NaOH, and other substances, and this finding is consistent with previous reports [23]. These impurities are residual sodium components (RSC).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S1) showed that the NNSO-E sample had the same peaks at 117, 166, and 1073 cm −1 as the Na 2 CO 3 that was also exposed to the air under the same conditions. Therefore, the impurities on the surface are possibly composed of Na 2 CO 3 •nH 2 O, NaHCO 3 •nH 2 O, NaOH, and other substances, and this finding is consistent with previous reports [23]. These impurities are residual sodium components (RSC).…”
Section: Resultssupporting
confidence: 92%
“…The superior cycle performance of the NNSO-E-H sample may be attributed to its clean surface. On the contrary, some RSCs, which adversely affect long-term cycle stability [23], can be found on the surface of pristine NNSO samples.…”
Section: Electrochemical Characterizationmentioning
confidence: 96%
“…Besides natural abundances and prices of raw materials, air stability also determines the commercialization of Na x TMO 2 . ,, An air-stable electrode material should maintain its structure, chemical composition, and electrochemical properties after exposure to a specific atmosphere for a given time . However, because of the lower charge density of Na + and lower redox potential, Na x TMO 2 materials display poorer air stability than their lithium counterparts.…”
Section: Redox-active Cations and Structures For Na X Tmo2mentioning
confidence: 99%
“…[7] Obviously, only by an in-depth exploration of the mechanism of changes in the surface and near-surface layers of Ni-rich CAMs after storage in air (the main influencing component factors are H 2 O and CO 2 ), can we effectively prevent or optimize the root cause. [1,[9][10][11][12]…”
Section: Introductionmentioning
confidence: 99%